2012
DOI: 10.1007/s00464-012-2556-1
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical study for assessment of incision characteristics and pain associated with LESS versus laparoscopic cholecystectomy

Abstract: The LESS single-port (SP) operations demand a bigger incision than LC surgery. However, there were no differences in healing, wound infections, and hernia development. We found a tendency of less postoperative pain associated with LESS/SP than with LC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 30 publications
1
31
3
Order By: Relevance
“…1,3,28 Although SILC outcomes largely depend on surgeon's skill, 2 the variety of the surgical techniques used in SILC could be responsible for the inconsistent rate of this complication. The mean diameter of the umbilical fasciotomy is about 3 to 4 cm to fit various types of multichannel ports, a most commonly used technique in SILC.…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3,28 Although SILC outcomes largely depend on surgeon's skill, 2 the variety of the surgical techniques used in SILC could be responsible for the inconsistent rate of this complication. The mean diameter of the umbilical fasciotomy is about 3 to 4 cm to fit various types of multichannel ports, a most commonly used technique in SILC.…”
Section: Commentsmentioning
confidence: 99%
“…The mean diameter of the umbilical fasciotomy is about 3 to 4 cm to fit various types of multichannel ports, a most commonly used technique in SILC. 28 Compared with the biggest fasciotomy (usually in the paraumbilical incision) about 1.2 to 2 cm in diameter in conventional multi-incision LC, the 3 to 4 cm umbilical fasciotomy in SILC could unsurprisingly enhance the incisional hernia rate. In contrast, our SIMPLY technique only leaves two 5-mm and a 10-mm facial punctures which are close to each other in vertical arrangement.…”
Section: Commentsmentioning
confidence: 99%
“…All but four were single-center trials [33,[35][36][37]. Twenty-two were published in the English language, and one was published in Spanish, which was translated by a Spanish native-speaking author [29].…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Ad hoc multiports were used in 13 studies. Curved instruments exclusively were used in 3 trials [27,33,39], and a combination of curved and linear instruments was applied in 7 [26,29,30,[34][35][36]40].…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Vidal et al (2011) [19] reported that the median VAS pain score one day after surgery was not significantly different in the SPLC group (3, range 1-5) compared with the MPLC group (4, range 1-8) (P=0.311). Madureira FA et al (2013) [20] concluded that the mean VAS score for pain at hour 3 was 2.0 points (0-7) for the SPLC group and 4.0 (0-10) for the MPLC group (p = 0.07), and at postoperative hour 24 it was 0.3 points (0-6) for LESS and 2.3 (0-10) for LC (p = 0.03). A randomised controlled study conducted by Mingwei Zheng et al (March 2012).…”
Section: Agementioning
confidence: 99%